Understanding the Coexistence of Adenomyosis and Uterine Fibroids in Patients with Endometriosis to Enhance Treatment and Fertility Outcomes - Hina Niaz; Dure Nayab; Asaf Alam Khan (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES